Biologisch abbaubare Werkstoffe Natur oder Petrochemie? - Mecking, Stefan (My University, 2004)
Naturally occurring polymers have been utilized for a long time as materials, however, their application as plastics has been restricted because of their limited thermoplastic processability. Recently, the microbial synthesis of polyesters directly from carbohydrate sources has attracted considerable attention. The industrial-scale production of poly(lactic acid) from lactic acid generated by fermentation now provides a renewable resources-based polyester as a commodity plastic for the first time. The biodegradability of a given material is independent of its origin, and biodegradable plastics can equally well be prepared from fossil fuel feedstocks. A consideration of the overall carbon dioxide emissions and consumption of non-renewable resources over the entire life-cycle of a product is not necessarily favorable for plastics based on renewable resources with current technology - in addition to the feedstocks for the synthesis of the polymer materials, the feedstock for generation of the overall energy required for production and processing is decisive.
Keywords: Grüne Chemie; Kunststoffe; Petrochemie; Polymere; Umweltchemie; 540